Development of a recombinant replication-deficient rabies virus-based bivalent-vaccine against MERS-CoV and rabies virus and its humoral immunogenicity in mice - Kato, Hirofumi; Takayama-Ito, Mutsuyo; Iizuka-Shiota, Itoe; Fukushi, Shuetsu; Posadas-Herrera, Guillermo; Horiya, Madoka; Satoh, Masaaki; Yoshikawa, Tomoki; Yamada, Souichi; Harada, Shizuko; Fujii, Hikaru; Shibamura, Miho; et al. (PloS one, 2019)
Middle East respiratory syndrome-coronavirus (MERS-CoV) is an emerging virus that causes severe disease with fatal outcomes; however, there are currently no approved vaccines or specific treatments against MERS-CoV. Here, we developed a novel bivalent vaccine against MERS-CoV and rabies virus (RV) using the replication-incompetent P-gene-deficient RV (RVΔP), which has been previously established as a promising and safe viral vector. MERS-CoV spike glycoprotein comprises S1 and S2 subunits, with the S1 subunit being a primary target of neutralizing antibodies. Recombinant RVΔP, which expresses S1 fused with transmembrane and cytoplasmic domains together with 14 amino acids from the ectodomains of the RV-glycoprotein (RV-G), was developed using a reverse genetics method and named RVΔP-MERS/S1. Following generation of RVΔP-MERS/S1 and RVΔP, our analysis revealed that they shared similar growth properties, with the expression of S1 in RVΔP-MERS/S1-infected cells confirmed by immunofluorescence and western blot, and the immunogenicity and pathogenicity evaluated using mouse infection experiments. We observed no rabies-associated signs or symptoms in mice inoculated with RVΔP-MERS/S1. Moreover, virus-specific neutralizing antibodies against both MERS-CoV and RV were induced in mice inoculated intraperitoneally with RVΔP-MERS/S1. These findings indicate that RVΔP-MERS/S1 is a promising and safe bivalent-vaccine candidate against both MERS-CoV and RV.